2018
DOI: 10.1371/journal.pone.0194841
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment tumour perfusion parameters and initial RECIST response do not predict long-term survival outcomes for patients with head and neck squamous cell carcinoma treated with induction chemotherapy

Abstract: ObjectivesPreviously, we showed that pre-treatment tumour plasma perfusion (Fp) predicts RECIST response to induction chemotherapy (ICT) in locoregionally advanced head and neck squamous cell carcinoma (HNSCC). The aim here was to determine whether the pre-treatment tumour Fp estimate, changes in tumour Fp or RECIST response post 2 cycles of ICT were prognostic for long-term survival outcomes.MethodsA prospective study enrolled patients with high stage HNSCC treated with docetaxel (T), cisplatin (P) and 5-fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Our results and those of earlier published reports support the notion that tumors with a high perfusion status might closely better to a good response. [25][26][27][28][29][30][31][32] Lowe et al 29 reported that high pretreatment tumor perfusion evaluated using pretreatment DCE-MRI imaging in HNSCC predicts a good response to neoadjuvant chemotherapy. Kim et al 9 reported that a higher pretreatment K trans in primary cancer may predict good treatment response in patients with HNSCC underwent chemoradiation, which both agreed with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and those of earlier published reports support the notion that tumors with a high perfusion status might closely better to a good response. [25][26][27][28][29][30][31][32] Lowe et al 29 reported that high pretreatment tumor perfusion evaluated using pretreatment DCE-MRI imaging in HNSCC predicts a good response to neoadjuvant chemotherapy. Kim et al 9 reported that a higher pretreatment K trans in primary cancer may predict good treatment response in patients with HNSCC underwent chemoradiation, which both agreed with our results.…”
Section: Discussionmentioning
confidence: 99%
“… 8–10 Although widely used to describe the regression status of a solid tumor, unidimensional measurement, such as RECIST, was not always a predictive value for the treatment outcome of head and neck cancer patients. 11 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Although widely used to describe the regression status of a solid tumor, unidimensional measurement, such as RECIST, was not always a predictive value for the treatment outcome of head and neck cancer patients. 11 On contrary, the extent of tumor volume shrinkage after IC has been established as a prognostic factor for other cancer. In rectal cancer, preoperative tumor volume reduction after chemoradiation therapy predict disease-free survival (DFS).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Although widely used to describe the regression status of a solid tumor, unidimensional measurement, such as RECIST, was not always a predictive value for the treatment outcome of head and neck cancer patients. [11] On contrary, the extent of tumor volume shrinkage after IC have been established as a prognostic factor for other cancer. In rectal cancer, preoperative tumor volume reduction after chemoradiation therapy predict disease free survival.…”
Section: Introductionmentioning
confidence: 99%